2022
DOI: 10.1088/1755-1315/1093/1/012017
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the wetland methane budget to estimate its transport to groundwater

Abstract: We are considering the methane budget for a taiga raised bog Mukhrino in order to estimate how much methane can potentially be transported from wetlands with the flow of groundwater. The production and oxidation of methane in the wetland, methane emission from the surface, accumulation in the gas phase in peat and migration with groundwater are distinguished as components of the wetland methane budget. The methane production is calculated using results of laboratory incubation experiments with peat, the oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
(40 reference statements)
0
0
0
Order By: Relevance
“…It should be noted that the median values of CH 4 flux from the hollow and the waterlogged hollow (6 and 11 mgCH4 m −2 h −1 , respectively) fall well within the range of methane emissions from hollows reported for Mukhrino earlier [24], although slightly exceed the median values. Also, according to static chamber observations in Mukhrino in August-September 2020 [25], methane emissions in hollows amounted to 3.7 ÷ 5.0 mgCH4 m − 2 h −1 , lower than during our campaign.…”
Section: Ch 4 Emissionscontrasting
confidence: 43%
See 1 more Smart Citation
“…It should be noted that the median values of CH 4 flux from the hollow and the waterlogged hollow (6 and 11 mgCH4 m −2 h −1 , respectively) fall well within the range of methane emissions from hollows reported for Mukhrino earlier [24], although slightly exceed the median values. Also, according to static chamber observations in Mukhrino in August-September 2020 [25], methane emissions in hollows amounted to 3.7 ÷ 5.0 mgCH4 m − 2 h −1 , lower than during our campaign.…”
Section: Ch 4 Emissionscontrasting
confidence: 43%
“…Mukhrino represents a typical landscape of an oligotrophic raised boreal peatland [4]. Earlier studies addressed both CO 2 [20][21][22] and CH 4 [23][24][25] fluxes at Mukhrino and stressed differences across the microlandscapes. Namely, it was found that the net exosystem exchange of CO 2 averaged over three growing seasons at the hollow site was significantly higher than at the ridge site.…”
Section: Introductionmentioning
confidence: 99%